REHABILITASI LAHAN KRITIS DI NTT MELALUI PENGEMBANGAN HUTAN KEMASYARAKATAN (HKm) - Yudhistira ANR Ora; Fransiskus Xaverius Dako (Politeknik Pertanian Negeri Kupang, 2016)
Critical land area in East Nusa Tenggara (ENT) comprises of relatively large area, which is 1,512,934.77 ha (83.64%) of the total 1,808,900 ha of the forest area in ENT Province; the category of critical comprises of potential to be critical to critical. The targets of the critical land are lands with function related to rehabilitation and reforestation activities, which include protected forests, protected areas outside the forest areas, and cultivated areas for agricultural purposes. To prevent forest and land destruction and to renew the function of the critical lands, actual efforts on forest and land rehabilitation are needed. According to the Ministry of Forestry Decree Number 20/Kpts-II/2001, the aim of critical land and forest rehabilitation is choosing degraded land and forest resources to be function optimally so that they can provide benefits for the people, guarantee the balance of environment and watershed systems and support the sustainability of forest development. In creating of sustainable forest management, there is a need of a model of forest management as a part of forest and degraded land rehabilitation; one of the efforts is through development of community forests.Â Â Community forests are state forests with main benefits are put on community empowerment, especially for community who live in and around forest areas. The community empowerment could be seen as efforts in improving community abilities and independencies so that they can be benefited from the forest resources optimally and fairly through capacity development and accessibility for the prosperity of the community.Keywords: reforestation, critical lands, community forests.